Ubiquitin‐independent proteasomal degradation of Spindlin‐1 by the E3 ligase HACE1 contributes to cell–cell adhesion. Issue 4 (2nd February 2021) - Palicharla, Vivek Reddy; Gupta, Devanshi; Bhattacharya, Debjani; Maddika, Subbareddy
Abstract : HECT‐E3 ligases play an essential role in catalyzing the transfer of ubiquitin to protein substrates. The noncatalytic roles of HECT‐E3 ligases in cells are unknown. Here, we report that a HECT‐E3 ligase, HACE1, functions as an adaptor independent of its E3 ligase activity. We identified Spindlin‐1, a histone reader, as a new HACE1‐associated protein. Interestingly, we found that HACE1 promotes Spindlin‐1 degradation via the proteasome in an ubiquitination‐independent manner. Functionally, we demonstrated that the loss of HACE1 results in weak cell–cell adhesion due to Spindlin‐1‐mediated accumulation of GDNF, a negative regulator of cell adhesion. Together, our data suggest that HACE1 acts as a molecular adaptor and plays an important noncatalytic role in presenting selected substrates directly to the proteasome for degradation. Abstract :